PURWARUPA ALAT PENDETEKSI OTOMATIS KETINGGIAN AIR UNTUK MENGATUR BUKA TUTUP PINTU AIR BERBASIS ARDUINO - M Roykhul Jinan; Agung Priyanto; Andika Bayu Saputra; Alfun Roehatul Jannah (Fakultas Teknik dan Teknologi Informasi, Universitas Jenderal Achmad Yani Yogyakarta, 2022)
With the increasing population and the reduction of water catchment areas due to numerous development projects that disregard green open spaces, coupled with a lack of public awareness regarding the importance of water flow, many individuals continue to consciously dispose of garbage into rivers, including river areas, dams, and reservoirs. This behavior leads to river blockages, resulting in flooding in those areas and other low-lying regions. The traditional method of monitoring water levels heavily relies on human operators, which can introduce errors when interpreting water indicators. To address these challenges, this research adopts a design-oriented methodology to develop an automated system for real-time maintenance and monitoring of water levels. The study begins with a comprehensive analysis of the existing issues and the underlying processes involved. Subsequently, the research focuses on designing and implementing a prototype system using appropriate materials, system development tools, and methodologies. The proposed system consists of a water level detection device integrated with a servo-controlled dam opener. Experimental tests demonstrate the device's effectiveness in accurately detecting changes in water levels, with an average accuracy of 10 cm from the sensor point. Additionally, the servo-controlled dam opener plays a significant role in regulating water flow within the system. The proposed system aims to facilitate efficient monitoring and decision-making processes, thereby reducing the occurrence of human errors in determining water levels.